The outlaws [compact disc, unabridged] - Griffin, W. E. B. (Griffin, W. E. B. Presidential Agent, 2010)
Charlie Castillo's secret unit has been disbanded, but that doesn't mean he's out of business. As experience has painfully shown him, there are many things the intelligence community can't do, and he has the men and assets to help set things straight. However, the danger of his next mission becomes apparent when he receives a FedEx package bearing photos of biohazard materials, which was supposed to have been destroyed during a raid on a secret Russian factory in the Congo.